Impaired Magnesium Protoporphyrin IX Methyltransferase (ChlM) Impedes Chlorophyll Synthesis and Plant Growth in Rice - Wang, Zhaohai; Hong, Xiao; Hu, Keke; Wang, Ya; Wang, Xiaoxin; Du, Shiyun; Li, Yang; Hu, Dandan; Cheng, Kexin; An, Baoguang; Li, Yangsheng (Frontiers in Plant Science, 2017)
Magnesium protoporphyrin IX methyltransferase (ChlM) catalyzes the formation of magnesium protoporphyrin IX monomethylester (MgPME) from magnesium protoporphyrin IX (MgP) in the chlorophyll synthesis pathway. However, no ChlM gene has yet been identified and studied in monocotyledonous plants. In this study, a spontaneous mutant, yellow-green leaf 18 (ygl18), was isolated from rice (Oryza sativa). This mutant showed yellow-green leaves, decreased chlorophyll level, and climate-dependent growth differences. Map-based cloning of this mutant identified the YGL18 gene LOC_Os06g04150. YGL18 is expressed in green tissues, especially in leaf organs, where it functions in chloroplasts. YGL18 showed an amino-acid sequence similarity to that of ChlM from different photosynthetic organisms. In vitro enzymatic assays demonstrated that YGL18 performed ChlM enzymatic activity, but ygl18 had nearly lost all ChlM activity. Correspondingly, the substrate MgP was largely accumulated while the product MgPME was reduced in ygl18 leaves. YGL18 is required for light-dependent and photoperiod-regulated chlorophyll synthesis. The retarded growth of ygl18 mutant plants was caused by the high light intensity. Moreover, the higher light intensity and longer exposure in high light intensity even made the ygl18 plants be more susceptible to death. Based on these results, it is suggested that YGL18 plays essential roles in light-related chlorophyll synthesis and light intensity–involved plant growth.